Role of career exploration in influencing career choice among pre-university student - Yusran, Noor Ashira; Mohd Puad, Mohd Hazwan; Omar, Muhd Khaizer (Universiti Putra Malaysia, 2021)
In the age of innovation, digitalization, and globalization today, deciding to take a career path has been growing and challenging. The career path continues to increase its stature as a career choice, pursued by many in an evolving, unpredictable, and competitive marketplace. Students’ general career selection process is the first step to ensuring that human resources align with the labor market demands. This study aimed to determine the role of career exploration as a mediator in the relationship between social support and career self-efficacy on career choices among pre-university students. This research is a quantitative and correlational study conducted on students in the Agricultural Science of Foundation program at Universiti Putra Malaysia. By using simple random sampling, 249 students were selected based on Cohen’s calculation. The researchers used the Career Exploration Survey (CES), Multidimensional Scale of Perceived Social Support, Career Decision-Making Self-Efficacy Scale-Short (CDSE-SF), and career choice instrument surveys to measure the variables in this study. The results show that career exploration acts as a partial mediator in the relationship between social support and career self-efficacy on career choice. There is not only a significant relationship between the career exploration and the career choice, but also some direct relationship between the social support, career self-efficacy and career choice. This study provides a basis for reference to academicians and instructors designing the pre-university student curriculum in choosing a career. Teachers are also recommended to play an active role in initiating career exploration activities for students during their learning process.